A Historical Review of Educational Technology: Evolving Definitions and Milestones (1970–2024) - Mohamed, Ahmed Abdi; Auliantika Selian (Indonesian Journal of Learning and Instructional Innovation, 2025)
This study provides a comprehensive historical analysis of educational technology from 1970 to 2024, highlighting significant transformations driven by technological advancements and evolving pedagogical paradigms. In the present study, the systematic literature review focuses on the evolution of definitions of educational technology and the identification of milestones. The study offers insights for educators, researchers, and policymakers in shaping future educational technology practices. It evolved over the years to encompass technology, media, communication, and learning systems, as well as systems approaches to instruction. Some of the major developments include the use of audio-visual aids in the 1970s, the use of personal computers in the 1980s, the use of internet and Learning Management Systems in the 1990s and the use of virtual reality, augmented reality and artificial intelligence in the 21st century. These developments show the advancement in educational technology and the impact it can have on the learning process.